The effectiveness study of SnCl2.2H2O masking on the formation of QCM profile using wet etching technique with KOH solution - Tri Andi Rusly; D.J. Djoko H. Santjojo; Setyawan P. Sakti; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2017)
SnCl2.2H2O has been successfully utilized to produce isotropic profile on the surface of a SiO2 crystall by a wet etching procces. The etching process was carried out by using a 40% KOH solution. In this research, the wet etching method is carried out by optimizing the etch time which was varied for 0,5 hour, 1 hour, 1,5 hour. The profile was determined by applying a SnCl2.2H2O on the surface of a QCM. The mask was applied by using a spray coating technique. The SnCl2.2H2O material was chosen as the masking material because it has a high adhesive property to SiO2, does not react to the KOH etching solution and is corrosion resistance as well as low cost. The etching profile surface results and etch depth (Dz) were determined using topography measurement system (TMS 1200). The etching rate with 40% KOH during etching time of 30 minutes, 60 minutes, 90 minutes were 4.36 μm, 4.56 μm and 5.79 μm respectively. The optimum QCM surface isotropic profile was obtained at the etching rate of 4.56 μm / h by 60 minutes etching.